2018
DOI: 10.1088/1361-6528/aaecbd
|View full text |Cite
|
Sign up to set email alerts
|

CMOS-compatible Si metasurface at visible wavelengths prepared by low-temperature green laser annealing

Abstract: A low-temperature laser crystallization is newly devised for producing polycrystalline silicon (poly-Si) thin films of low-loss, low surface roughness enough for nanoscale patterning, applicable to practical Si metasurface elements on complementary metal-oxide semiconductor (CMOS) electronic architectures in visible lights. The method is based on dielectric encapsulation of an amorphous Si film and subsequent laser-induced local crystallization. Such poly-Si thin film yields order-of-magnitude smaller surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The primary materials used for dielectric metasurfaces include Si, GaN, TiO 2 , and SiN x . Si is an abundant element and can be easily processed using standard CMOS-compatible manufacturing techniques [117][118][119][120][121]. Therefore, Si-based metasurfaces are regarded as low-cost metasurface platforms.…”
Section: Si-based Metasurfacesmentioning
confidence: 99%
“…The primary materials used for dielectric metasurfaces include Si, GaN, TiO 2 , and SiN x . Si is an abundant element and can be easily processed using standard CMOS-compatible manufacturing techniques [117][118][119][120][121]. Therefore, Si-based metasurfaces are regarded as low-cost metasurface platforms.…”
Section: Si-based Metasurfacesmentioning
confidence: 99%
“…In contrast, it is found that an arbitrary phase delay can also be provided by subwavelength structures based on various mechanisms, such as electromagnetic resonance and geometric phase [1,2]. The related area, termed as a metasurface with planar features, has attracted increasing attention due to its flexible design scheme and great reduction in fabrication burden [3,4]. In particular, by elaborately manipulation the phase delay distribution, metasurfaces can act as a metalens with a single focus or multifocal function [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%